A novel sea surface evaporation scheme assessed by the thermal rotating shallow water model - Masoud Rostami; Stefan Petri; Bijan Fallah; Farahnaz Fazel‐Rastgar (Atmospheric Science Letters)
Abstract In this study, a novel sea surface evaporation scheme, along with its corresponding bulk aerodynamic formulation, is proposed to estimate sea surface evaporation, columnar humidity, and precipitation distribution within the atmosphere. The scheme is based on three distinct functions, each dependent on a single variable: zonal wind velocity, tropospheric (potential) temperature, and free convection. It is shown that the normalized Clausius–Clapeyron formula requires an adjustable scaling factor for real‐world applications, calibrated using empirical fitness curves. To validate the proposed approach, we employ a model based on the pseudo‐spectral moist‐convective thermal rotating shallow water model, with minimal parameterization over the entire sphere. ECMWF Reanalysis 5th Generation (ERA5) reanalysis data are used to compare the model's results with observations. The model is tested across different seasons to assess its reliability under various weather conditions. The Dedalus algorithm, which handles spin‐weighted spherical harmonics, is employed to address the pseudo‐spectral problem‐solving tasks of the model.